Radar Wing Defender (RWD): Sistem untuk membantu para petani dalam mendeteksi dan pengusir hama burung - Fawwaz Mulya Rabbani Fawwaz; Rafi Fadhlurrahman; Nadira Eka Putri; Raihan Akmalano; Galih Alif Artanto; Rahmat Hidayat (Sultan Publisher, 2025)
Around 90% of Indonesia's population uses rice as food. However, the production process has not been able to fully fulfil the needs of the community, due to several obstacles that affect productivity. Bird pests are one of the main causes of rice disruption. Group birds are known as one of the few pests that tend to cause population problems. The purpose of this research is to get the design of an IoT-based rice bird repellent. This IoT-based bird repellent consists of two main parts: hardware, or hard system, and software, or soft system. An ESP32 microcontroller and ultrasonic sensors are used in this prototype. This Bird Pest Prototype can be hammered automatically. As a result, the existence of this prototype makes it easier for caregivers to treat patient wounds in case of pest injuries; however, this can be done more effectively and efficiently because caregivers do not need to visit the fields to treat patient wounds due to various pest injuries. Based on this prototype, if the ultrasonic sensor detects a bird with a range of 0 to 4 metres, the buzzer will sound, and the servo motor will move the lever to bring the radar-detected bird closer.